Physiotherapy And Rehabilitation Center - Okal, Hala (My University, 2018)
The proposed site is located east of Nablus, near Hisham Hijjawi College. The total area is 24 dunums . The site is easily accessible by public transport, easy access from the surrounding villages, the location is quiet, and the area of the site is commensurate with the design and functional requirements, as well as the slope is 1.13%. Concept: Philosophy concept: - The dynamic and movement are the essence of physiotherapy methods through exercise; this is why the dynamic track was, to encourage users to move through it. - Rehabilitation centers are the link between hospitals and homes, so the design provides healing environment and comfortable environment. Strategy concept: - In the design of the track and to make it obvious, it designed in a same language, which is walls and ramps. - The site has been planned and the location of the walls based on the functional spaces to be provided, which are medical zone, rehabilitation zone, sports and recreational zone, in addition to the service and administrative zone. - The direction of walls is north south direction to suit the direction of playgrounds and swimming pool, as well as the direction of one of the site's borders. Functions Medical Spaces: contains receptions spaces and physiotherapy rooms with different methods of massage, exercises, wet therapy, and dry therapy. Rehabilitation Spaces: contains workshops for many professions, such as cooking, carpentry, electronics and sewing. Sports and recreational spaces: contains outdoor and indoor courts and cafeteria. Administrative spaces: contains offices, public relations, volunteer unit, archives and accounting, in addition to the office of the director and secretary